DIVERSED ETHNOMATHEMATICS EXPLORATIONS OF BATAK CULTURES IN NORTH SUMATERA - Br Ginting, Siti Salamah; Simanjorang, Mangaratua; Gultom, Syawal (Ethnomathematics Journal, 2024)
The Batak ethnic group has cultural diversity and is rich in the values of each culture, both in the products and processes, and cultural philosophies. The Batak ethnicity is divided into several sub-ethnicities, including Toba Batak, Karo Batak, Mandailing Batak, and Simalungun Batak. The distinctive characteristics of each ethnicity can be used as material for research by researchers to explore the elements of that culture. In the field of mathematics, culture can also be used as an object of study. The research method used in the present study is the systematic literature review (SLR) which is aimed at identifying, studying, evaluating, and interpreting research results by the topics being studied so that it will answer the research questions that have been determined. The results can be seen that the Batak ethnic cultural components have mathematical concepts in them such as, among others,  livelihood characters, traditional houses, traditional musical instruments, traditional foods, ulos cloth and ornaments. traditional dances, and traditional clothing. The mathematical concepts that are obtained from the exploration of Batak ethnic cultures include the concepts of lines, angles, congruence, spatial geometry, flat geometric shapes, spatial geometric shapes, geometric transformations, arithmetic sequences, and numbers. These diverse themes indicate that mathematics is our culture.